NEW AND FEW KNOWN SPECIES OF BRACHYURA FROM AMBON - Serene, Raoul; Moosa, M. K. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1971)
The present material corresponds to a part of a collection made in Ambon by the senior author. The collection was made during a survey conducted (September 1970) by the Institute of Marine Research of Indonesia (see Serene 1971) and is deposited in this Institute in Djakarta.